Fomento à autocomposição de conflitos e sustentabilidade - Brandão, André da Fonseca (My University, 2020)
The culture of autonomous conflict resolution is being encouraged in Brazil as an integrated element to Judicial System and procedural reforms, and the autonomous methods of resolution are seen as an alternative path, less costly and more effective, to providing the demand for justice that once remained concentrated in the juditial path. The State takes, increasingly, a legal stance of consensus towards civil society. It turns to social participation in decision making and public activity control. Under a parameter of sustainability, it is recommended that access to justice takes a multicultural form, that decision making be inclusive and responsive, that solutions are adequate to local reality and that citizen responsibility is attributed to collectivity and its components. Departing from such manifestations of sustainability, and through their constrast with the potential of autonomous forms of conflict resolution, one can conclude that there is a reciprocal influence between the fomentation of autonomous conflict resolution and the principle of sustainability. Encouraging autonomous conflict resolution interferes positively in increasing sustainability, given that a successful culture of selfcomposition increases inclusiveness, responsiveness, and access to justice. At the same time, selfocomposition methods and fomentation towards them should be influenced to aim at its sustainability building potentials, which rely less on perfecting the juditial system, through settlements, and more in empowering citizens, amplifying actual access to justice, developing a rationality based on the other and constructing social capital in private iniciative, families, communities, and collectivities.
A cultura de autocomposição de conflitos vem sendo fomentada no Brasil como elemento integrado às reformas do Poder Judiciário e do processo judicial, visualizando-se os métodos autônomos de resolução como via alternativa de atender, com menor custo e maior efetividade, a demanda por justiça outrora concentrada na via jurisdicional. O Estado, por sua vez, assume uma posição jurídica crescentemente consensual. Volta-se à participação da sociedade na tomada de decisão e controle das atividades (inclusive administrativas) de interesse coletivo. Sob o prisma da sustentabilidade multidimensional, recomendam-se a busca pelo acesso à justiça em uma feição multiculturalista, a tomada de decisão responsiva e inclusiva, a construção de soluções adequadas à realidade local, o reconhecimento de autonomia e a atribuição de responsabilidade cidadã à coletividade e seus integrantes. A partir de tais manifestações, contrastadas com as potencialidades inerentes aos métodos autônomos de resolução de conflitos, conclui-se que há uma relação de interinfluência entre o fomento à autocomposição de conflitos e o princípio da sustentabilidade. O fomento à autocomposição influencia potencialmente, de forma positiva, a sustentabilidade, uma vez que a cultura bemsucedida de autocomposição agrega inclusão, responsividade e acesso à justiça. Ao mesmo tempo, devem os métodos de autocomposição, tanto quanto o fomento em direção à sua prática, sofrer influência do mesmo princípio. Por isso, deve manter o foco específico na produção de resultados sustentáveis, que se voltam menos ao aperfeiçoamento do Sistema Judiciário, por meio de acordos, e mais ao empoderamento cidadão, à ampliação material do acesso à justiça, ao desenvolvimento da racionalidade de alteridade e à construção de capital social em âmbito privado, familiar, comunitário e coletivo.
Keywords: Conciliação (Processo civil); Mediação; Negociação; Sustentabilidade; Conciliation (Civil procedure); Mediation; Negotiation; Sustainability